Penerapan Tata Kelola Teknologi Informasi pada PT Pelita Transfer Nusantara Berdasarkan Kerangka Kerja Cobit 2019 - Desyolanda Manullang; Suprapto Suprapto; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
PT Pelita Transfer Nusantara is a company engaged in Remittance (foreign currency exchange) which was founded by Crisman Wise Patuan Silaban in 2018. Transfree. To achieve its goals, PT Pelita Transfer Nusantara cooperates with many third parties and is very dependent on the available resources so that it requires good management and management of IT resources. Considering that the elements in IT resources are not only infrastructure but also human resources, good HR management and management will greatly support the company in achieving its goals optimally. It is necessary to evaluate the existing IT governance at PT Pelita Transfer Nusantara to assess the extent to which PT Pelita Transfer Nusantara manages its IT and human resources. Based on these needs, research was conducted to identify the level of capability and condition of the company's current IT resource management using the COBI 2019 framework, the APO07 (Managed Human Resource), APO08 (Managed Relationships) and BAI08 (Managed Knowledge) processes. Data collection in this study was carried out using an assessment sheet questionnaire, interviews, and observations. The respondents of this research are the Chief Product Officer and Chief Executive Officer of the company which are determined based on the RACI Chart. The Capability level achieved by PT Pelita Transfer Nusantara is currently level 2 in the APO07 and BAI08 processes, and level 1 in the APO08 process. The recommendations given focus on activities in managing minimum vacation time, staff reserve, improving human resource skills and competencies, maintaining awareness of relationship activities, and using and assessing knowledge.